Mechanically stimulated osteochondral organ culture for evaluation of biomaterials in cartilage repair studies. (November 2018) - Vainieri, M.L.; Wahl, D.; Alini, M.; van Osch, G.J.V.M.; Grad, S.
Graphical abstract: Abstract: Surgical procedures such as microfracture or autologous chondrocyte implantation have been used to treat articular cartilage lesions; however, repair often fails in terms of matrix organization and mechanical behaviour. Advanced biomaterials and tissue engineered constructs have been developed to improve cartilage repair; nevertheless, their clinical translation has been hampered by the lack of reliable in vitro models suitable for pre-clinical screening of new implants and compounds. In this study, an osteochondral defect model in a bioreactor that mimics the multi-axial motion of an articulating joint, was developed. Osteochondral explants were obtained from bovine stifle joints, and cartilage defects of 4 mm diameter were created. The explants were used as an interface against a ceramic ball applying dynamic compressive and shear loading. Osteochondral defects were filled with chondrocytes-seeded fibrin-polyurethane constructs and subjected to mechanical stimulation. Cartilage viability, proteoglycan accumulation and gene expression of seeded chondrocytes were compared to free swelling controls. Cells within both cartilage and bone remained viable throughout the 10-day culture period. Loading did not wear the cartilage, as indicated by histological evaluation and glycosaminoglycan release. The gene expression of seeded chondrocytes indicated a chondrogenic response to the mechanical stimulation. Proteoglycan 4 and cartilage oligomeric matrix protein were markedly increased, while mRNA ratios of collagen type II to type I and aggrecan to versican were also enhanced. This mechanically stimulated osteochondral defect culture model provides a viable microenvironment and will be a useful pre-clinical tool to screen new biomaterials and biological regenerative therapies under relevant complex mechanical stimuli. Statement of Significance: Articular cartilage lesions have a poor healing capacity and reflect one of the most challenging problems in orthopedic clinical practice. The aim of current research is to develop a testing system to assess biomaterials for implants, that can permanently replace damaged cartilage with the original hyaline structure and can withstand the mechanical forces long term. Here, we present an osteochondral ex vivo culture model within a cartilage bioreactor, which mimics the complex motion of an articulating joint in vivo . The implementation of mechanical forces is essential for pre-clinical testing of novel technologies in the field of cartilage repair, biomaterial engineering and regenerative medicine. Our model provides a unique opportunity to investigate healing of articular cartilage defects in a physiological joint-like environment.